MALARIA PADA KEHAMILAN DAN KONSEKUENSINYA PADA IBU DAN JANIN - Rahmah, Zainabur (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2017)
Malaria is an infectious disease remains a major health problem in the world. Malaria attacks without differentiating individual age and sex of pregnant women are no exception. Pregnant women have a risk of malaria by Plasmodium parasites is more severe in comparison with non-pregnant women. When a pregnancy will occur immunosuppression both humoral and cellular purpose of this paper is to discuss the mechanism of occurrence of malaria in pregnancy and its consequences on the mother and fetus. Parasite adhesion receptors Chondroitin Sulfate A (CSA) and Hyaluronic Acid (HA) in the placenta can trigger an inflammatory process involving the secretion of cytokines. Inflammatory component that appears after the accumulation of parasites in the placenta is associated with immune pathology in the Pregnancy-Associated Malaria (PAM), such as thickening of the membrane cytotrophoblasts that disrupt blood flow, inhibiting the transfer of IgG across the placenta and the exchange of nutrients from mother to fetus, causing lesions in the placenta. Malaria infection during pregnancy is a process of mediation by protein cytoadherence in Plasmodium falciparum erythrocyte membrane protein-1 (PfEMP-1) encoded by genes that bind to receptors on Var2CSA this causes placental sequestration of infected erythrocytes on endothelial cells resulting in anemia in pregnant while on fetus causes low birth weight, premature birth and stillbirth.